On Language Cognition Relations and Evolution of Language - Fatma Ebru Köse (Psikiyatride Güncel Yaklaşımlar, 2023)
One can understand the importance of language with its relation to mental activities such as memory and thinking. Language, a crucial human ability, has long attracted the attention of various theorists and philosophers. Language, by its nature, interacts with many biological, cultural and psychological factors. This article has drawn a general framework by bringing together the views from disciplines such as linguistics, psychology, anthropology, biology and neuroscience. On the one hand, while the theoretical opinions about language are included, on the other hand, language is discussed in the context of the changes we went through by separating from our common ancestor in the evolution process. When dealing with language, it is possible to talk about our differences from animals, the interaction of language with our cognitive processes and its organization in the brain. The views put forward by philosophers such as Plato and Descartes about the relationship between language and cognitions have expanded by Chomsky, Pinker, Dunbar and others on the evolution of language. In this article, evolutionary psychology, which strives to understand language and its relationship with cognitions, is emphasized by combining the data of modern evolutionary biology and cognitive psychology. Language is acquired quickly and without the intense need for learning experiences, thanks to innate schemas, suggests that evolution formed these schemas. According to another view, the influence of the environment and culture gains importance instead of innatism. In addition, different opinions on the evolution of language are briefly discussed. Discussion topics include triggers of language development in evolution. These are related to biological and cultural influences, influences of vocalization and hand gestures on language. When thinking about language and its evolution, it is inevitable to observe and examine cognitive processes and thought. Multidisciplinary studies can also provide important information about the evolution of language while trying to understand the complex relationship between language and cognition.